Expression of anion exchanger 2 in human gastric cancer - Yang, Y.; Wu, P.P.; Wu, J.; Shen, W.W.; Wu, Y.L.; Fu, A.F.; Zheng, L.; Jin, X.L.; Fu, G.H. (Experimental Oncology, 2008)
Anion exchanger 2 (AE2), which mediates exchange of Cl-/HCO3- across the plasma membrane, is widely expressed in body tissues. It is most abundantly expressed in stomach and is responsible for the uptake of Cl- ions that are destined to become HCl molecules. Aim: To determine whether AE2 expression was altered in gastric tumors. Methods: We have studied AE2 expression in normal human gastric tissues (n =16) and in gastric tumors (n = 33) using immunohistochemistry and immunofluorescent labeling. Results: In normal gastric tissue positive staining was observed in gastric fundus gland, suggesting parietal cell-related expression of AE2, and AE2 expression was localized in the nuclear membrane and even in cell nuclei. For assay of cancerous gastric tissues, specimens of human gastric cancer arising from the region of the fundus (2 cases), the body (14 cases) and the antrum (17 cases) were randomly selected. Immunohistochemical staining has showed that AE2 was down-regulated in all 14 cancerous gastric body specimens, whereas staining for AE2 in cancerous antrum was less intense and had a diffuse profile. Conclusions: The data suggest that AE2 might be associated with gastric carcinogenesis and the achlorhydria experienced by gastric cancer patients. Анионный обменник 2 (АЕ2), который опосредует перенос Cl-
/HCO3
-
через плазматическую мембрану, экспрессируется
клетками разных тканей. Самый высокий уровень экспрессии АЕ2 в желудке, поскольку этот белок отвечает за поглощение
ионов Cl-
, которые впоследствии используются для секреции HCl. Цель: Изучить изменения в экспрессии АЕ2 при раке
желудка. Методы: исследована экспрессия АЕ2 в нормальных тканях (n = 16) и опухолях желудка (n = 33) с применением
методов иммуногистохимии и иммунофлуоресценции. Результаты: в нетрансформированной ткани желудка в фундальной
железе выявляли сильную положительную реакцию, что свидетельствует об экспрессии АЕ2 париетальными клетками,
причем экспрессия АЕ2 была локализирована в ядерной мембране и в ядре. В опухолях желудка (фундального отдела (n =
2), тела (n = 14) и антрального отдела (n = 17)), отобранных случайным образом, был проведен анализ экспрессии АЕ2.
Иммуногистохимическое исследование показало снижение экспрессии АЕ2 во всех 14 случаях рака тела желудка. Окрашивание
АЕ2 в образцах рака антрального отдела желудка было менее интенсивным и диффузным. Выводы: полученные
данные позволяют предположить наличие связи между экспрессией АЕ2 и развитием рака желудка, а также ахлоргидрией,
отмечаемой у больных раком желудка.